Shopping with Allah: Muslim pilgrimage, gender and consumption in a globalised world - Thimm, Viola (UCL Press, 2023)
Shopping with Allah illustrates the ways in which religion is mobilised in package tourism and how spiritual, economic and gendered practices are combined in a form of tourism where the goal is not purely leisure but also ethical and spiritual cultivation. Focusing on the intersection of gender and Islam, Viola Thimm shows how this intersection develops and changes in a pilgrimage-tourism nexus as part of capitalist and halal consumer markets. Based on extensive ethnographic fieldwork in Malaysia, the United Arab Emirates and Oman, Thimm sheds light on how Islam and gender frame Malaysian religious tourism and pilgrimage to the Arabian Peninsula, but she raises many issues that are of great importance beyond these regional contexts. This book also offers an innovative methodological-analytical toolkit to research mobility and intersectionality across socio-geographic scales ‘Scaling Holistic Intersectionality’. By bringing methodological holism into a fruitful engagement with the antiracist-feminist framework intersectionality, Thimm argues that hierarchical relationships, i.e. marginalisation, power and empowerment, can shift for an individual or a social group depending upon the social sphere. Shopping with Allah will primarily be of interest to readers within the anthropology of gender, the anthropology of Islam and the anthropology of religion more broadly.